PENGEMBANGAN APLIKASI KLIK ME! SEBAGAI MEDIA LAYANAN KONSELING RAMAH DISABILITAS DI ERA SOCIETY 5.0 - Sari, Fera Puspito (UIN Sunan Kalijaga Yogyakarta, 2023)
Along with digital transformation in the era of society 5.0, counseling services can be carried out indirectly through the internet network and using a communication medium called cyber counseling. The development of digital counseling service applications is expected to be the right innovation to create inclusive e-counseling services. This study uses the Research and Development (RnD) method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). But, this research conducted only reached the development stage. Data collection techniques using observation, interviews, and questionnaires. The results of this study indicate that the Klik Me! Application the counselee contains dashboard menus, assessment lists, consultation schedules, live chat and announcements. The results of the feasibility assessment of media experts were 86.7%, material experts 92.5%, non-disabled counselees 83% and 89% disabled counselees, this shows that the application Klik Me! very worthy to use. Click Me App! It is also considered as disability-friendly media that is accessible for blind and deaf people. Keywords: disability friendly, Klik Me! application, media counseling